4p-3forx=3

Simple and best practice solution for 4p-3forx=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4p-3forx=3 equation:


Simplifying
4p + -3forx = 3

Reorder the terms:
-3forx + 4p = 3

Solving
-3forx + 4p = 3

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-4p' to each side of the equation.
-3forx + 4p + -4p = 3 + -4p

Combine like terms: 4p + -4p = 0
-3forx + 0 = 3 + -4p
-3forx = 3 + -4p

Divide each side by '-3orx'.
f = -1o-1r-1x-1 + 1.333333333o-1pr-1x-1

Simplifying
f = -1o-1r-1x-1 + 1.333333333o-1pr-1x-1

Reorder the terms:
f = 1.333333333o-1pr-1x-1 + -1o-1r-1x-1

See similar equations:

| 3(-5.4n+1)+5.6n=26.5 | | 2x+5+5x=-12 | | =84 | | 5log-7m+4=-6 | | 25+3x-x=x+4 | | 50=2(15+x) | | M-5=150 | | x^3+12x^2-5x=0 | | .35s+.6(30-s)=.45(30) | | 3y+4=8-(y+6) | | 6x-80=160 | | 34(6-7x)=4x+9 | | 0.65+0.33t=3.63t-0.67 | | 3p^2=6p | | 15z=90 | | 14+-2(3p+1)=6(4+p) | | -5x-3x+1=-14 | | -3(-4-4x)=72 | | ok= | | Sinx=.5299 | | x^2-8x+16=-x^2+20 | | 6x+8y=260 | | 16=1.6x | | 3p^2=2p | | 3(4e-7)=27 | | 2x+8y-16w= | | 3x^2+21x-4x=218 | | Sinx=.8660 | | 2(x^2-4x-2)=0 | | 1/6k+2k=65/8 | | 2x^2+4x-12=x^2+4x+24 | | 10x-3x+20=4x+53 |

Equations solver categories